Keanekaragaman Undur-Undur Laut (Anomura: Hippidae) Dari Kepulauan Banda - Nurulvadini Safrudin; Ali Suman; Nisfa Hanim; Achmad Farajallah (Institut Pertanian Bogor, 2023)
Mole crabs are part of the superfamily Hippoidea and members of the family Hippidae Latreille,1825, which inhabit sandy beaches, particularly the swash zone. This condition is commonly found in the Banda Islands. The purpose of this research was to determine the species diversity of the genus Hippa Fabricius, 1787 in the Banda Islands. We identified the species by its morphological characters. Sample collection was done by purposive sampling method. Based on the study's findings, four of the five previously reported species in Indonesia were identified. Hippa ovalis (A. Milne-Edwards, 1862), H. adaactyla Fabricius, 1787, H. marmorata (Hombron & Jacquinot, 1846), and H. celaeno (De Man, 1896) were the species obtained. Hippa cf. ovalis and Hippa cf. marmorata are both presumed to be new species. This study includes descriptions of the two species. Keywords: distribution, Hippidae, Hippa, intertidal, sandy substrate